Presence of Hepatozoon spp in free-living spectacled caiman (Caiman crocodilus) in Madre de Dios, Peru - Carlos Erazo, Nancy (2020)
The aim of this study was to determine the presence of Hepatozoon sp in free-living spectacled caiman (Caiman crocodilus) in Bajo Madre de Dios, located in the department of Madre Dios, Peru. Blood samples were taken from 30 individuals (21 males, 4 females, 5 of undetermined sex) from three age categories (sub-adult, adult and reproductive active adult). The alligators were captured on the bank of the Bajo Madre de Dios river. Two smears per sample were prepared, fixed with methanol and stained with May-Grunwald Giemsa. The biometric measurements of the gametocytes, both intra and extra-erythrocytic were determined, confirming their correspondence with the genus Hepatozoon. The results showed that 90% (27/30) of the individuals were positive for Hepatozoon sp, being 100% females (4/4), 95.2% (20/21) of males and 60.0% (3/5) of undetermined sex.